2018
DOI: 10.1177/0300985818767996
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus Infection in Quail

Abstract: Newcastle disease (ND), caused by virulent strains of Newcastle disease virus (NDV), is a devastating disease of poultry worldwide. The pathogenesis of ND in quail is poorly documented. To characterize the ability of virulent NDV strains to replicate and cause disease in quail, groups of 14 two-week-old Japanese quail ( Coturnix japonica) were experimentally inoculated with 10 EID (embryo infectious dose 50%) units of 1 of 4 virulent NDV strains: 2 isolated from quail ( N2, N23) and 2 from chickens ( Israel, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…These clinical signs were progressed in intensity at 7 dpi and involved more quails. The neurological clinical signs as a result of tropism of virulent NDV strains to the nervous tissues were also previously reported (Ecco et al, 2011;Susta et al, 2018). Our results showed that the quails inoculated by NDV VIId failed to develop a severe systemic infection in comparison to NDV VIb, although using the same dose (10 7 EID 50 /quail) as well as the same route (oculo-nasal route).…”
Section: Discussionsupporting
confidence: 85%
“…These clinical signs were progressed in intensity at 7 dpi and involved more quails. The neurological clinical signs as a result of tropism of virulent NDV strains to the nervous tissues were also previously reported (Ecco et al, 2011;Susta et al, 2018). Our results showed that the quails inoculated by NDV VIId failed to develop a severe systemic infection in comparison to NDV VIb, although using the same dose (10 7 EID 50 /quail) as well as the same route (oculo-nasal route).…”
Section: Discussionsupporting
confidence: 85%
“…Backyard chicken, geese, and ducks which are naturally less susceptible to virulent NDV are also incriminated in maintaining the virus in the environment [ 50 ]. Furthermore, exotic pet birds kept in close proximity to commercial poultry have been shown to harbour virulent NDV strains that are genetically highly related to those obtained in the commercial farms [ 51 ]. This occurrence of virulent NDV in apparently healthy wild and backyard poultry not only constitutes a huge diagnostic challenge but also represents a big biosecurity threat to the commercial poultry industry.…”
Section: Diagnosismentioning
confidence: 99%
“…Most of the research into NDV is done as viral challenge models in chickens or in ovo using SPF embryonated chicken eggs, but the strain of chicken and the precise definition of SPF are not often disclosed [444,[478][479][480][481][482][483]. The most commonly reported strain of chicken used is the White Leghorn, along with others such as White Rock and Isa Brown layers [120,447,[484][485][486]. It is known that differences in the innate immune response in differing breeds of chicken can have drastic effects on the response to infection [487], making this important in describing the model.…”
Section: Newcastle Diseasementioning
confidence: 99%